Phosphonated graphene oxide-modified polyacrylamide hydrogel electrolytes for solid-state zinc-ion batteries. (10th December 2022) - Abbasi, Ali; Xu, Yaolin; Abouzari-Lotf, Ebrahim; Etesami, Mohammad; Khezri, Ramin; Risse, Sebastian; Kardjilov, Nikolay; Van Tran, Khanh; Jia, Haojun; Somwangthanaroj, Anongnat; Manke, Ingo; Lu, Yan; et al.
Abstract: Compared to rigid batteries using liquid electrolytes, solid-state batteries (SSBs) offer several advantages: flexibility, prevention of leakage, suppression of dendritic formation and hydrogen evolution, as well as minimization of cathode active material dissolution. For the materialization of real-life SSBs, gel polymer electrolytes (GPEs) are among promising candidates. However, development of GPEs with satisfying ionic conductivity and mechanical endurance is challenging. Herein, we report on the development of polyacrylamide (PAM)/phosphonated graphene oxide (PGO) nanocomposite hydrogel electrolytes for zinc-ion batteries; PGO acts as the filler through in-situ polymerization of acrylamide in an aqueous suspension of PGO. The synthesized PAM/PGO hydrogel exhibits high ionic conductivity of 31.0 mS/cm at 30 °C compared to that of PAM (13.8 mS/cm) and PAM-GO (20.8 mS/cm). The higher ionic conductivity of PAM-PGO can be attributed to its higher hydrophilicity and electrolyte storage capacity along with its lower activation energy for ionic conduction (7.2 KJ/mol K) in comparison with that of PAM (10.1 KJ/mol K) and PAM-GO (10.2 KJ/mol K). The interaction between water against PAM, PAM-GO and PAM-PGO is investigated via density-functional theory (DFT). The MnO2 -based zinc-ion battery assembled using PAM-PGO as electrolyte shows high initial capacity of 240 mAh/g, losing only 4 and 15% of its capacity after 100 and 145 cycles, respectively. Results demonstrate promising potential of PAM-PGO as a solid-state electrolyte for flexible battery applications.